Potensi Pengembangan Komoditas Teripang Pasir (Holothuria scabra Jaenger) secara Berkelanjutan dengan Model Integrasi Sea Farming di Kepulauan Padaido Kabupaten Biak Numfor - Daniel Lantang; Yunus P. Paulangan (Jurnal Biologi Papua, 2015)
Sea cucumber is one of high value economic commodity due to not only having a fairly completed nutrition, but also used as the raw material for production of drugs, cosmetics and others. Therefore it becomes one of the highly potential export commodities. However, the target of catching sea cucumbers community intensively will give a negative impact on its sustainability. Sea cucumber has long been recognized and protected by the people in Padaido islands known as sasisen or sasi system. Although it has been conserved through sasisen system, but tends decline recently. This happen due to the high fishing activities by fisherman. Sea farming methods is a sea fisheries development concept in shallow waters such as the merger between aquaculture and capture fisheries by utilizing leading commodity in potential cultivation area. Sea farming is a system of utilization of marine ecosystem-based marine culture with the ultimate goal to improve the stock of fish (fish resources enhancement) to the sustainability of fisheries and other marine-based activities such as ecotourism. This paper will discuss the development opportunities of sea farming system that is integrated with the prevailing of local wisdom in Padaido Islands, Biak Numfor Regency, Papua, namely sasisen. This system works in conserving sea cucumber resources and increasing incomes of local communities in Padaido island through the creation of alternative livelihoods specifically in sea cucumber cultivation. Therefore, these models and approaches can be considered to manage coastal and marine resources in a sustainable way in Padaido Islands, Biak Numfor Regency.Key words: Sea cucumber, sustainable management, sasisen, Padaido Islands.